PROTECTIVE EFFECTS OF HIBISCUS SABDARIFFA LINN EXTRACT ON OXIDATIVE STRESS AND COLLAGEN DEPOSITION IN D-GALACTOSE-INDUCED SKELETAL MUSCLE AGING IN RATS - Gabriella E.O Andrianti; Nurul Paramita; Roman Ardian Goenarjo; Imelda Rosalyn Sianipar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Background: The aging process in skeletal muscle is often triggered by chronic oxidative stress that impacts extracellular matrix remodeling in the form of fibrosis and decreased motor function. Hibiscus sabdariffa Linn. (HSL) extract is known to be rich in polyphenol and anthocyanin compounds that have the potential as antioxidant agents. Objective: This study aims to analyze the potential of HSL intervention in regulating gastrocnemius muscle aging in an old rat model accelerated with D-galactose, reviewed from molecular, histopathological and functional aspects. Methods: A total of 18 rats were divided into three groups (n=6): Young Normal Group (NM), D-galactose aging acceleration Group (Ap), and D-galactose + HSL Group (ApH). Aging induction was carried out using D-galactose at a dose of 200 mg/KgBW, daily for 8 weeks orally via tube. HSL supplementation was mixed in drinking water at a dose of 400 mg/KgBW daily for 8 weeks. The parameters tested included serum Malondialdehyde (MDA) levels, MMP-9 levels in muscle tissue, limb muscle grip strength, and the percentage of collagen deposition in histopathology preparations. Results: MDA levels and MMP-9 enzyme activity in the Ap group were higher than the NM group (P < 0.001). The percentage of gastrocnemius muscle tissue collagen in the Ap group was lower than the NM group (P < 0.05). No differences were found in muscle grip strength between the Ap group and the NM group. MDA and MMP-9 levels in the ApH group given HSL supplementation were not significantly different from the NM group (P > 0.05). The percentage of gastrocnemius muscle tissue collagen in the ApH group was also not significantly different from the NM group (P > 0.05). Conclusion: Supplementation of HSL extract in the accelerated aging group was able to suppress MDA levels, reduce MMP-9 levels, and maintain the percentage of gastrocnemius muscle tissue collagen. Hibiscus sabdariffa Linn. extract proven to be effective in inhibiting the aging process of gastrocnemius muscle through the mechanism of lipid peroxidation chain cleavage and prevention of fibrotic remodeling, which contributes to the maintenance of the mechanical functional capacity of the muscle.